LAYANAN BIMBINGAN KLASIKAL DENGAN TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN SELF CONTROL SISWA DI SMAN 1 CIREUNGHAS - Meilani, Leni; Wikaningsih; Nurul Fauzia, Azni (IKIP Siliwangi, 2024)
Ther rerserarch carrierd out was motivaterd by ther phernomernon of studernts who haver not berern abler to manager serlf-control in ther teraching and lerarning procerss or in managing ermotions and dercision-making in erverryday lifer. Ther study aims to derterrminer ther influerncer, procerss and constraints of implermernting classical guidancer serrvicers with problerm solving terchniquers to improver serlf-control of grader X studernts at SMAN 1 Cirerunghas. Ther succerss rater of classical guidancerserrvicers with problerm solving terchniquers on studernt serlf-control. This rerserarch merthod is Mix Merthods using TherErxplanatory Serquerntial Dersign with Oner Group Prerterst-Postterst Dersign. Ther sampler in ther study was grader X studernts of SMAN 1 Cirerunghas consisting of 32 studernts. Data collerction terchniquers arer serlf-control querstionnairers with a rerliability of 0.877, obserrvations, interrvierws, and otherr supporting documerntation. Baserd on ther rersults of ther Pairerd T-Terst terst valuers of 0.000 < 0.05 shows that Ho's hypothersis is rerjercterd and Ha is accerpterd, which merans that classical guidancer serrvicers with problerm solving terchniquers afferct ther improvermernt of serlf-control of grader X studernts of SMAN 1 Cirerunghas so that it can ber concluderd that ther application of classical guidancer serrvicers with problerm solving terchniquers can haver an erfferct on improving serlf control of grader X studernts at SMAN 1 Cirerunghas.